Systematic Review on Quality of Life of Patients with Chronic Kidney Disease - J. Parekh, Arpita; HN. , Ravindra (International Journal of Psychosocial Rehabilitation, 2020)
Background: QOL is an overall assessment of a person’s well-being, which may include physical, emotional, and social dimensions, as well as stress level, sexual function, and self-perceived health status. End-stage renal failure is a chronic disease that exerts a great negative impact on patients’ health-related QOL, mainly due to the accompanied impairment or to the imposed limitations in almost all domains of their daily lives. Despite remarkable advances in the treatment of HD, the patients encounter certain physical, psychological, economic, and social problems that affect their QOL. Objectives: This review aims to examine systematically the impact of patient navigator training on the quality of life of patients with chronic kidney disease undergoing hemodialysis to identify: (i) QOL of patients with CKD undergoing hemodialysis (ii) QOL of patients with CKD undergoing hemodialysis in terms of client-centered health education, meditation, and progressive muscle relaxation techniques. Methodology: Searches were conducted across 10 electronic databases using consistent keywords. Papers were screened by the title and abstract (n=733) and judged against predefined eligibility (n=26). Twenty-six papers were included in the review. Results: Different patient navigator training approaches were included, such as client-centered health education to improve knowledge related to disease conditions and meditation programs that include pranayama, progressive muscle relaxation techniques, and mindful meditation, which may indirectly impact quality of life (physical health, psychological health, social relationships, and environment). Patient navigator training may improve the quality of life of patients with chronic kidney disease undergoing hemodialysis. Conclusion: Few studies reported an effect on QOL (n=18); the lack of a clear theoretical framework resulted in ambiguous predictions about training and its effect. Methodological issues also constrain the strength of the evidence, including small sample sizes; an absence of blinding of participants and outcome assessors; and a lack of active control groups.